2020
DOI: 10.1177/0954407020969495
|View full text |Cite
|
Sign up to set email alerts
|

Layered control of forklift lateral stability based on Takagi–Sugenofuzzy neural network

Abstract: An anti-roll hydraulic cylinder is designed as an executive mechanism of the lateral stability control to provide lateral support force on the basis of an analysis of the structure of the forklift and the mechanism of lateral instability. A lateral stability layered control method based on Takagi–Sugeno (T–S) fuzzy neural network is proposed, divides the forklift lateral stability control into the upper identification layer, the middle control layer and the lower executive layer. Simulation and real vehicle te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Owing to the unique structure of a forklift and its low-speed and heavy-duty operating conditions compared with traditional road vehicles, this study adopts the anti-rollover support cylinder and full hydraulic active steering as the control system's actuator. 6 The anti-rollover support cylinder is a double-acting double-piston rod hydraulic cylinder. Both ends of the locking cylinder are hinged with the body and the rear axle, the upper and lower cavities are connected, and the external connecting oil circuit is provided with a locking solenoid valve.…”
Section: Anti-rollover Actuator Of the Counterbalance Forkliftmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the unique structure of a forklift and its low-speed and heavy-duty operating conditions compared with traditional road vehicles, this study adopts the anti-rollover support cylinder and full hydraulic active steering as the control system's actuator. 6 The anti-rollover support cylinder is a double-acting double-piston rod hydraulic cylinder. Both ends of the locking cylinder are hinged with the body and the rear axle, the upper and lower cavities are connected, and the external connecting oil circuit is provided with a locking solenoid valve.…”
Section: Anti-rollover Actuator Of the Counterbalance Forkliftmentioning
confidence: 99%
“…The relevant literature has indicated that when a forklift truck is empty and the position of the body centroid is backward, the forklift driving safety threshold is the minimum. 6 Therefore, the current study uses the most dangerous no-load condition for test and simulation.
Figure 11.Schematic of European standard runway for forklift stability.
…”
Section: Simulation Verification and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Papers published so far such as [22][23][24][25][26][27][28], explicitly deal with fork or whole forklift damage. In contrast, this paper is about understanding the mechanism of load damage on the forks of a forklift, which requires studying the individual nature of the forklift movement.…”
Section: Mechanism Of Load Damage Occurrencementioning
confidence: 99%